Perlindungan Hukum Bagi Pekerja yang Mengalami Kecelakaan Kerja Berdasarkan Undang Undang Cipta Kerja - Fery Firmansyah; Anggreany Haryani Putri; Arifin Arifin (Journal of Industrial Relations Studies, 2026)
Pasal 27 Ayat 2 of the 1945 Constitution of the Republic of Indonesia states, "Every citizen has the right to obtain employment and a decent living." Occupational safety is a concept and effort to ensure the integrity and perfection of human beings, both physically and spiritually, as well as their work and culture, aimed at the welfare of humanity in general and the workforce in particular.. Furthermore, the company's responsibility for workers experiencing a work-related accident is to provide compensation for transportation costs, examination, medical and/or treatment costs, rehabilitation costs, and monetary compensation. Legal protection for workers in the event of a work-related accident is provided by the Employment Social Security Agency (BPJS Ketenagakerjaan), which provides financial compensation to replace a portion of lost or reduced income and services resulting from a work-related accident